Higher adherence to core food-based vegetarian and prudent dietary patterns is associated with lower adiposity and metabolic disease risk in Pacific and New Zealand European women - Renall N; Merz B; Douwes J; Corbin M; Slater J; Firestone R; Kruger R; Te Morenga L (MaryAnn Liebert, 2026)
Background: Dietary patterns are linked to obesity and metabolic health. Aim: To explore associations between dietary patterns, adiposity, and metabolic syndrome risk in Pacific and New Zealand (NZ) European women. Methods: Pacific (n = 126) and NZ European (n = 161) women aged 18–45 years from Auckland were recruited based on BMI (normal weight and obesity) with approximately half in each ethnic group. Body fat percentage (BF%) was assessed with DXA and used to stratify participants into low (<35%) or high (≥35%) BF% groups. Dietary intake was assessed using a 5-day food record and semi-quantitative food frequency questionnaire, analyzed with the National Cancer Institute method. Dietary patterns were derived using principal component analysis. Fasting blood was analyzed for insulin, glucose, and lipids. Metabolic syndrome was defined using harmonized criteria. Results: Four dietary patterns were identified: Vegetarian, Processed, Prudent, and Keto. Regression analysis controlling for ethnicity, age, socioeconomic deprivation, energy intake, and physical activity showed that higher adherence to Vegetarian and Prudent patterns characterized by “core” foods was inversely associated with BF% and visceral fat% (p < 0.05). Higher adherence to Processed and Keto patterns (characterized by “discretionary,” and less “core” foods, respectively) was positively associated with BMI, BF%, and visceral fat% for both ethnic groups. Every 1 unit increase in adherence to the Processed pattern was associated with 50% higher odds of metabolic syndrome (OR: 1.53 [95% CI: 1.02, 2.30], p = 0.042). Conclusion: Greater adherence to “core” food patterns was associated with lower adiposity and metabolic disease risk, while patterns high in processed “discretionary” foods and less diversity of “core” foods were associated with higher metabolic risk.
Keywords: Diet; eating patterns; adiposity; obesity; metabolic syndrome; socioeconomic factors